Somalia : Enhanced Heavily Indebted Poor Countries (HIPC) Initiative-Decision Point Document. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents an assessment of Somalia's eligibility for assistance under the enhanced Heavily Indebted Poor Countries (HIPC) Initiative. The macroeconomic framework reflects the policy framework underlying the proposed three-year Fund-supported program. The debt relief analysis (DRA) remains largely unchanged, but some of the underlying debt data has been updated to reflect new information from creditors. In addition, this paper presents an assessment of debt management capacity in Somalia and a full Debt Sustainability Analysis under the Debt Sustainability Framework for Low-Income Countries. The DRA reveals that, after traditional debt relief mechanisms are applied, Somalia's debt burden expressed as the net present value of debt-to-exports ratio is 344.2 percent at the end of December 2018-significantly above the HIPC Initiative threshold. Despite the challenging environment, progress on reform and policy implementation has been good and sustained reforms have translated into economic results. In addition to the coordinated support from the World Bank and the IMF, reforms have been supported by other development partners.